Highly Porous Fluorescent Materials Based on Polymer Matrices Impregnated with Eu(dbm)3 Molecules in a Supercritical Carbon Dioxide Medium; Russian Journal of Physical Chemistry B; Vol. 14, iss. 7 - Rybaltovskii A. Aleksey; Akovantseva A. A. Anastasiya; Bolbasov E. N. Evgeny Nikolaevich; Buznik V. M. Vyacheslav Mikhaylovich; Zavorotny Yu. S. Yuriy; Minaev N. V. Nikita Vladimirovich; Mirochnik A. G. Anatoliy; Sergeev A. A. Aleksandr Aleksandrovich; Tverdokhlebov S. I. Sergei Ivanovich; Yusupov V. I. Vladimir Isaakovich (2020, 2020)
Title screen